Piezoelectric Energy Harvesting System to Charge Batteries with the Use of a Portable Musical Organ - Josué Esaú Vega-Ávila; Guillermo Adolfo Anaya-Ruiz; José Joel Román-Godínez; Gabriela Guadalupe Esquivel-Barajas; Jorge Ortiz-Marín; Rogelio Gudiño-Valdez; Hilda Aguilar-Rodríguez (Energies)
In recent years, the increase in energy demand has been an incentive to search for new ways to generate energy. An alternative is producing this energy from daily human activities. To do this, piezoelectric devices have been used in different human activities to collect energy. Some of these potential activities are transportation, biomedicine, and electronic devices. Harvesting energy from the mechanical force applied by a pianist during their performance is one of these activities that can be used. The implementation of piezoelectric devices under the keys of an electric organ was carried out. A theoretical model was developed to estimate the amount of energy we could recover. The system was characterized by controlled forces. The volume generated by the forces was measured via a Musical Instrument Digital Interface (MIDI) using the open-source music production software “LMMS (Linux MultiMedia Studio) 1.2.2 version”. The electric potential difference was measured as a function of the volume generated by the pianist. The voltages generated for different frequencies of the pianist’s rhythm were studied. The efficiency calculated in the mathematical model agreed with that obtained in the implemented system. The study results indicate that the batteries were recharged, which resulted in 53 s of organ operation.